2023
DOI: 10.1111/cns.14464
|View full text |Cite
|
Sign up to set email alerts
|

The role of NMDARs in the anesthetic and antidepressant effects of ketamine

Liang Zhou,
Jingjing Duan

Abstract: BackgroundAs a phencyclidine (PCP) analog, ketamine can generate rapid‐onset and substantial anesthetic effects. Contrary to traditional anesthetics, ketamine is a dissociative anesthetic and can induce loss of consciousness in patients. Recently, the subanaesthetic dose of ketamine was found to produce rapid‐onset and lasting antidepressant effects.AimHowever, how different concentrations of ketamine can induce diverse actions remains unclear. Furthermore, the molecular mechanisms underlying the NMDAR‐mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 174 publications
0
2
0
Order By: Relevance
“…This cascade results in enhanced regional activity of the excitation network, including changes in neuroplasticity, which leads to increased synaptogenesis and synaptic potentiation in the limbic system. Another study reported that ketamine’s antidepressive effect through the NMDARs is controversial [ 82 ]. The advantage of ketamine compared to other traditional antidepressants is its rapid antidepressive action (for several days) in patients with major depressive disorder (MDD).…”
Section: Depressionmentioning
confidence: 99%
“…This cascade results in enhanced regional activity of the excitation network, including changes in neuroplasticity, which leads to increased synaptogenesis and synaptic potentiation in the limbic system. Another study reported that ketamine’s antidepressive effect through the NMDARs is controversial [ 82 ]. The advantage of ketamine compared to other traditional antidepressants is its rapid antidepressive action (for several days) in patients with major depressive disorder (MDD).…”
Section: Depressionmentioning
confidence: 99%
“…Numerous reviews in recent years have offered explanations of the role of NMDAR in depression (Amidfar et al, 2019;Hanson et al, 2023;Zhou and Duan, 2023). It is important to use novel methods to uncover underlying connections and trends given the abundance of research in this field.…”
Section: Introductionmentioning
confidence: 99%